2011
DOI: 10.1088/0268-1242/27/1/015003
|View full text |Cite
|
Sign up to set email alerts
|

Electrical, spectral and optical performance of yellow–green and amber micro-pixelated InGaN light-emitting diodes

Abstract: Micro-pixelated InGaN LED arrays operating at 560 and 600 nm, respectively, are demonstrated for what the authors believe to be the first time. Such devices offer applications in areas including bioinstrumentation, visible light communications and optoelectronic tweezers. The devices reported are based on new epitaxial structures, retaining conventional (0 0 0 1) orientation, but incorporating electron reservoir layers which enhance the efficiency of radiative combination in the active regions. A measured outp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
20
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 25 publications
1
20
0
Order By: Relevance
“…1] is observed as the injection current is increased. Both the screening of the quantum-confined Stark effect in polar QWs and the band-filling effect can lead to this blueshift, and a detailed investigation of the relevant physics along with the numerical stimulation results has been reported [1]. Fig.…”
Section: Device Fabricationmentioning
confidence: 97%
See 2 more Smart Citations
“…1] is observed as the injection current is increased. Both the screening of the quantum-confined Stark effect in polar QWs and the band-filling effect can lead to this blueshift, and a detailed investigation of the relevant physics along with the numerical stimulation results has been reported [1]. Fig.…”
Section: Device Fabricationmentioning
confidence: 97%
“…To implement the micro-display system, we fabricate a dedicated micro-pixel LED array from this InGaN structure, interface it to a CMOS driver array and show direct display performance and color tuning under the CMOS control. Our InGaN material contains high (0.4) indium mole-fraction quantum wells, and we have recently reported the physics of color tuning in this material [1]. Further measurement shows that the modulation bandwidth of these integrated micro-LED/CMOS tunable pixels reaches 100 MHz, thus also providing a wavelength-agile source for high speed visible light communications.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…15 Gong et al experimentally and numerically demonstrated the electrical, spectral, and optical performances of yellow-green and amber micro-pixelated InGaN LEDs to gain insight into the responsible mechanisms of dualwavelength emission. [16][17][18] Based on these researches, the properties of light-emission and dynamics of carrier transportation in the dual-wavelength InGaN/GaN MQW LEDs were further clarified. In addition to the important issues of color rendering index (CRI), carrier localization due to the indium-rich nanostructures, and difficulty in growth of high indium-content alloys, there are some other significant problems which need to be solved toward the commercial realization of dual-wavelength monolithic InGaN MQW LEDs.…”
mentioning
confidence: 99%
“…26 Moreover, a broad-band LED with a shallow first well, which plays the role of prestrain layer or electron reservoir layer, is also explored and compared. [16][17][18]24 For the exploration of spectral competition between the green and violet emissions, the spontaneous emission rates as a function of wavelength for the four LEDs under study at 20, 100, 180, and 260 mA are depicted in Fig. 2.…”
mentioning
confidence: 99%